Optimum Design of Oil Tank Foundation on Different Soil Conditions - Ling Ngee Leh, Felix; Anuar, Nur Najwa Irdina; Abu Talib, Mohd Khaidir (Journal of Sustainable Underground Exploration, 2022)
Tank foundation is a base for the tank which is designed to support the weight of oil tanks and contain spillage. Other than that, tank foundation failure usually occurred when the foundation system cannot support the weight of the tank or the soil in that area is not improved, and failure of tank foundation can lead to pivoting effect and cracking on the foundation slab. This study aims to determine the deformation characteristics of foundation slab of oil tank foundation and evaluate the performance of oil tank foundation on different soil conditions. The oil steel tank with dimension of 27.68 m in diameter and 12 m high with 2000 kN of load was chosen from A Case Study of Study on Design of Ring Footing for Oil Storage by Alkhuzaie (2018). However, manual calculation for the slab thickness, pile cap self-weight, pile spacing, pile capacity and number of require pile were calculated manually as shown in appendix 2. Series of analysis with a finite element model was conducted using STAAD Foundation CONNECT Edition V9 was to analyse the foundation structure, observed the soil bearing capacity sensitivity and deformation characteristics of the foundation slabs. Three types of foundation (raft, pile raft and pile foundation) were designed in STAAD Foundation CONNECT Edition V9. From this study, the most optimum design for foundation structures with different soil conditions was obtained which are raft foundation structure is the most appropriate to construct on residual soil. In addition, pile raft foundation structure is the most appropriate to construct on marine sediment deposit while pile foundation structure on peat soil.